Community Engagement in Chinese and American Gold Mining Companies: A Comparative Case Study in Ghana - Yang Jiao (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper by Jiao Yang presents the results of field research examining local engagement and impact on local communities by a Chinese company and an American company operating in Ghana. Golden Sunshine Mining Company Ltd., a large-scale Chinese gold mining corporation is a relatively young company and is just starting to venture into the world of corporate social responsibility. It relies on local expertise in its engagement with the local community, and so far it has had a limited impact on local labor recruitment. Meanwhile, Newmont Ghana Gold Limited, an American company that has operated in Ghana for over ten years, has developed a robust local governance structure for supporting community development projects. Although locals seem to expect this level of effort from mining companies, Golden Sunshine does not prioritize community development.
Keywords: 330